Improving adherence to HIV quality of care indicators in persons with opioid dependence: the role of buprenorphine. - Korthuis, P Todd; Fiellin, David A; Fu, Rongwei; Lum, Paula J; Altice, Frederick L; Sohler, Nancy; Tozzi, Mary J; Asch, Steven M; Botsko, Michael; Fishl, Margaret; Flanigan, Timothy P; Boverman, Joshua; et al. (Journal of acquired immune deficiency syndromes (1999), 2011)
Opioid-dependent HIV-infected patients are less likely to receive HIV quality of care indicators (QIs) compared with nondependent patients. Buprenorphine/naloxone maintenance therapy (bup/nx) could affect the quality of HIV care for opioid-dependent patients.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Buprenorphine; Cohort Studies; Female; Guideline Adherence; HIV Infections; Humans; Male; Middle Aged; Multivariate Analysis; Naloxone; Narcotic Antagonists; Opiate Substitution Treatment; Opioid-Related Disorders; Practice Guidelines as Topic; Quality of Health Care